Impact of metabolic syndrome on the progression of coronary calcium and of coronary artery disease assessed by repeated cardiac computed tomography scans. Issue 1 (December 2016) - Kim, Lee; Yoon, Ji; Lee, Dong-Hwa; Kim, Kyoung; Choi, Sung; Park, Kyong; Jang, Hak; Kim, Min-Kyung; Park, Hyo; Choi, Su-Yeon; Lim, Soo
Abstract Background It is not clear how severe metabolic syndrome (MS) affects the development of coronary atherosclerosis. Methods This was an observational, retrospective cohort study with Koreans who received health check-ups voluntarily. A total of 2426 subjects had baseline and follow-up coronary artery calcium score (CACS) data. Among them, 1079 had coronary computed tomography angiography (CCTA) data. We compared baseline CACS and any progression in subjects with and without MS. A more detailed analysis was conducted for coronary artery disease (CAD), which was defined by coronary artery stenosis (≥50 %), multivessel involvement, and coronary plaques in those patients with CCTA data. Results At baseline, subjects with MS (34.0 %, n  = 825) had higher CACS and more significant coronary artery stenosis, multivessel involvement, and atheromatous plaques than those without MS (P  < 0.05 for all). In the follow-up (median 1197 days), subjects with MS showed significant increases in CACS and progression of CAD compared with counterparts without MS, in parallel with the numbers of MS components. Finally, MS was a significant predictor for the progression of CACS (hazard ratio 1.32; 95 % confidence interval 1.06–1.64) and progression of coronary artery stenosis and/or development of vulnerable plaque (hazard ratio 1.47, 95 % confidence interval 1.01–2.15) after adjusting for other cardiovascular risk factors. Conclusions Subjects with MS showed progression of CAD as assessed by CACS and CCTA over ~3 years. Therefore, more vigilant screening for coronary vascular health is needed among those with MS.